Leopold Kompert, conciliador de facções judaicas na Mitteleuropa - Krausz, Luis (Contingentia, 2009)
This article deals with two short stories by Leopold Kompert (1822-1886), a Jewish author from the Austro-Hungarian Empire and one of the major names in a genre which became known as Ghettoliteratur. As all other authors in his genre, Kompert dealt mainly with the conflicts involved in the passage from the world of traditional Jewry towards 19th into modernity. But he did this in a typical Habsburg way. Rather then emphasizing the incompatibility between these two worlds, Kompert tries, on the one hand, to preserve the memory of the vanishing world of the Jewish Shtetl, and on the other hand to create a synthesis between this world and the multi-lingual and multi-cultural Austro-Hungarian Empire.